Now is everything - Giles, Amy (Amy S.) (HarperTeen, an imprint of HarperCollins Publishers, 2017)
The McCauleys look perfect on the outside, but this family is hiding a dark secret. Hadley will do anything to keep her sister safe from their father. When Hadley's forbidden relationship with Charlie Simmons deepens, the violence at home escalates. An explosive accident occurs, following which Hadley attempts to take her own life at the hospital. Her friends, doctors, family, and the investigator on the case want to know why. Only Hadley knows what really happened that day, and she's not talking.--Provided by Publisher.